The landscape of recurrent spontaneous abortion registered on clinical trials.gov - Zhou, Xiaoling; Lai, Fan; Chen, Wei; Zhou, Congrong; Deng, Yi; Wang, Tao; Xing, Shasha; Diao, Haoyang; Tang, Mi; Guo, Wenmei; Luo, Erdan (Frontiers in Endocrinology, 2024)
ObjectiveRecurrent spontaneous abortion (RSA) presents a significant challenge in the field of reproductive medicine, as effective treatments remain limited despite extensive research efforts. A comprehensive understanding of current RSA clinical trials is essential for enhancing trial design and identifying existing research gaps. The aim of this study is to characterize RSA related clinical trials registered on Clinical Trials.gov.MethodsA thorough search was conducted to identify and review clinical trials focusing on RSA that were registered on Clinical Trials.gov up to March2, 2024.ResultsA total of 138 trials were identified in the analysis, with 72 (52.17%) classified as intervention trials and 66 (47.83%) as observational trials. Approximately half of the studies (67,48.55%) had an enrollment of 100 participants or fewer. The majority of trials included only female participants. Asia hosted the highest number of clinical trials (46,33.33%), followed by Europe (36,26.09%), Africa (29,21.01%), America (13,9.42%). The majority of trials (61,44.20%) focused on individuals with unexplained recurrent spontaneous abortion (URSA). The predominant intervention types examined in the reviewed studies were drug interventions (49,62.82%), with a notable rise in behavioral intervention trials.ConclusionOur research findings suggest that existing research efforts in the realm of RSA are inadequate for the progression of prevention and treatment strategies. The majority of clinical trials have primarily targeted individuals with URSA, with a particular emphasis on drug interventions, notably anticoagulants.